Traditional Governance in Nepal’s Majhi Communities: A Case Study of Majhesawa in Sindhupalchok and Ramechhap Districts - Paudel, Laxman (International Research Journal of MMC, 2024)
Customary self-government system of the indigenous Majhi community called Majhesawa is at the stage of extinction and its remnants can be found in Sindhupalchok and Ramechhap districts. The aim of this research is to explore current situation of Majhesawa in Sindhupalchok and Ramechhap districts. The design of the study was qualitative in Nature. 70 participants were selected using a purposive sampling method from Sindhupalchok and Ramechhap districts. Primary data were collected using Focused Group Discussion and in-depth interview as data collection tools in 2024, and secondary data were collected reviewing different literatures. It is found that in both districts, forming Majhesawa committees is being conducted as a campaign with the understanding that all the problems that appear in the Majhi community can be solved at the community level by protecting and promoting the rights and interests of the Majhi. Active participation of youths, elders and women is seen in this campaign. Although Majhesawa committees have been formed in most of the Majhi settlements, all committees are inactive due to lack of written documents and knowledge about duties, responsibilities and rights. Majhesawa committees are performing their role especially during the Koshi Puja. In both districts, the Majhesawa committees have not received legal recognition from any government body so far and there has been no effort from the Majhi community to do so. It seems that organizations related to Majhi community and people related to Majhesawa should take the initiative to obtain legal recognition to operate Majhesawa and prepare necessary procedures and documents. This article can be useful to the social workers and political leaders.